The Authority of Fatwa in Islamic Law: Between Legitimacy and Implementation - Muhammadong Muhammadong (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The authority of fatwa in Islamic law is essential in directing the legal and moral behavior of Muslims. This study investigates the intricate dynamics of fatwa authority, emphasizing the equilibrium between its legality and its application in modern Islamic communities. The research investigates the historical underpinnings of fatwa issuance, examining the methodologies and standards used by religious scholars and organizations in the promulgation of fatwas. It also looks at the problems that come up when trying to put fatwas into practice in today's world, such as the role of governmental institutions, the many ways that Islamic scholars interpret them, and the changing demands of society. This study seeks to comprehend the legitimization and application of fatwas within various Muslim communities by a critical examination of legal and socio-political issues, while also evaluating the efficacy of fatwas in influencing contemporary Islamic legal practices. This research closes by offering ideas to augment the relevance and efficacy of fatwas within modern Islamic legal frameworks.